2002
DOI: 10.1021/ol0165894
|View full text |Cite
|
Sign up to set email alerts
|

Redox Refunctionalization of Steroid Spiroketals. Structure Correction of Ritterazine M

Abstract: The structure of the North spiroketal moiety of ritterazine M has been corrected from 1a to 1b. This was accomplished by comparison of published spectra of the natural product with five synthetic spiroketal-alcohols. Synthesis of these models was efficiently accomplished by reductive cleavage of the spiroketal and Sharpless asymmetric dihydroxylation of an isopentyl, methyl 1,1-disubstituted olefin, followed by Suarez iodine[III] oxidative spirocyclization of monoprotected 1 degree,3 degree 1,2 diols.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
19
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(20 citation statements)
references
References 14 publications
1
19
0
Order By: Relevance
“…The correlation originally showed that the biological activities of cephalostatins 8 and 16 and ritterazine M appeared substantially out of place 62. In all three instances, the structures had been assigned incorrectly 81. The calculation method also correctly predicted that compounds 23′-deoxy cephalostatin 138 and 17′-OH-23′-deoxy cephalostatin 137 would exhibit activity within a factor of 10 of cephalostatin 1 ( 1 ) (Figure 20).…”
Section: Structure Activity Relationshipsmentioning
confidence: 95%
“…The correlation originally showed that the biological activities of cephalostatins 8 and 16 and ritterazine M appeared substantially out of place 62. In all three instances, the structures had been assigned incorrectly 81. The calculation method also correctly predicted that compounds 23′-deoxy cephalostatin 138 and 17′-OH-23′-deoxy cephalostatin 137 would exhibit activity within a factor of 10 of cephalostatin 1 ( 1 ) (Figure 20).…”
Section: Structure Activity Relationshipsmentioning
confidence: 95%
“…In the original paper ritterazine M ( 686 ) was erroneously assigned as the S configuration at C-22, along with an incorrect configuration at C-12 [ 330 ]. A chemical synthesis of this compound by Fuchs et al allowed correcting the structure [ 331 ]. Ritterazines A ( 672 ), T ( 673 ), D ( 676 ), E ( 677 ), N ( 687 ), O ( 688 ), U-X ( 693–696 ), and Z ( 697 ) have a unique five-membered C ring on their right side, which is a rearranged steroid nucleus, the same as Veratrum alkaloids.…”
Section: Basic Skeletal Classificationmentioning
confidence: 99%
“…To synthesize 4 / 6 from diosgenin ( 1 ), we need to replace three C–O bonds (C16–O, C22–O, and C26–O) with C–N bonds, two of which should proceed stereoselectively, and to epimerize the configuration of C25. It was reported that the ring F of diosgenin ( 1 ) could be opened reductively to give the C22 R -configured furostanol 14 , based on which we devised our synthetic plan (Scheme ). We envisioned that the C26–N bond of solanidine ( 4 ) could be constructed via an intramolecular N -alkylation and C22–N be established through an intramolecular Schmidt reaction of azide 13 followed by a substrate-controlled reduction of the resultant imine 11 .…”
Section: Introductionmentioning
confidence: 99%